Enhancing Iraqi EFL Learners' Writing Skills by Using Cooperative Language Teaching Approach at Open Educational College - Rawdhan , Lecturer. Sameerah Mohsin (Manar Elsharq Journal for Literature and Language Studies, 2026)
In order to help second-year university students at Open Educational College improve their writing abilities, a cooperative language learning (CLL) strategy was adopted to enhance peer learning. Students in CLL-based groups were taught to take more ownership of their education by honing both their interpersonal and language skills in a more laid-back social setting. Students enrolled in the first course of the 2023 academic year's first semester received this therapy. A pre-post writing test and an attitude questionnaire were the two instruments employed in this investigation. A Wilcoxon test was used to compare the pre- and post-test results using descriptive statistics. Examining students' work for errors in spelling, vocabulary use, grammar, punctuation, and coherence was a major focus of the evaluation process. The results showed that, at the significance level of.001, the students' writing scores were higher for the post-test than the pre-test following this type of intervention. The results of the attitude scale showed that the students had positive attitudes regarding using the cooperative learning strategy to improve their language proficiency in general and their writing proficiency in particular.